Дослідження роботи шнекового прес-екструдера в парі з багатосекційним пристроєм формування паливних брикетів - Самойчук, Кирило Олегович; Самохвал, Віталій Анатолійович; Samoichuk, Kyrylo; Samokhval, Vitalii (Запоріжжя : ТДАТУ, Видавничий дім «Гельветика», 2025)
UA: Актуальність цього дослідження обумовлена гострими проблемами, з якими стикаються виробники паливних брикетів, що використовують як сировину відходи оліємістких культур. Більша частина пресового обладнання не дає змоги без включення в лінію додаткового обладнання виготовляти якісний продукт із цього типу сировини. Тому ці дослідження спрямовані на вирішення проблеми щодо зменшення відсоткової частки олій у готовому продукті та збільшення часу перебування сировини у стиснутому стані завдяки додаванню секцій пристрою формування паливних брикетів. Таким чином, поставлену мету роботи – покращення якості готової продукції та збільшення ресурсу пресового обладнання – було виконано. За результатами проведених досліджень було визначено, що розроблений шнековий прес екструдер у парі з пристроєм остаточного формування зі здатністю відбору олій на етапі формування брикету має підвищену ефективність порівняно з традиційними. EN: The relevance of this study is due to the acute problems faced by most fuel briquette producers that use oilseed waste as a raw material. Currently, the world market offers a wide range of press equipment that operates efficiently when processing raw materials that do not contain oil or contain a small amount of oil (straw, reeds, wood waste). However, there is not a large number of industrial equipment capable of working with oil-containing feedstocks and providing good quality fuel briquettes that do not contain a central hole. The large time of pressing equipment does not allow to produce a quality product from this type of raw material without including additional equipment in the line. During pressing, the waste is exposed to high pressure, which is accompanied by an increase in temperature. It is this thermal effect that promotes the active release of lignin, which, hardening after cooling, ensures the strength of the finished product. As a result, the briquettes have high mechanical strength, which makes them resistant to external influences, and the dense surface structure of the briquettes reduces their hygroscopicity and facilitates convenient transportation and long-term storage. Our research is aimed at solving the problem of reducing the percentage of oils in the finished product and increasing the time of stay of raw materials in a compressed state due to the number of sections of the fuel briquette forming device. One of the goals of the work is to improve the quality of the finished product and increase the service life of the press equipment. After analyzing the operation of the existing press equipment and its shortcomings, it was decided to develop a wicker screw press extruder paired with an extended final molding device with the ability to dose oils at the briquette formation stage.
Studying the operation of a screw press extruder in combination with a multi-sectional fuel briquette forming device
Keywords: олія; брикет; прес; формування; достискання; сировина; лігнін; oil; briquette; press; molding; ripening; raw materials; lignin